Worldwide interethnic variability and geographical distribution of CYP2C9 genotypes and phenotypes - Céspedes-Garro, Carolina; Fricke-Galindo, Ingrid; Naranjo, María Eugenia G; Rodrigues-Soares, Fernanda; Fariñas, Humberto; de Andrés, Fernando; López-López, Marisol; Peñas-Lledó, Eva M; LLerena, Adrián (Expert opinion on drug metabolism & toxicology, 2015)
Introduction: Notably differences in CYP2C9 allele frequencies among worldwide populations have been reported, with an interesting low frequency of the CYP2C9*2 allele in Amerindians compared with Admixed and European populations. Areas covered: Literature was searched using the PubMed database and was focused on worldwide original research papers on CYP2C9 alleles and CYP2C9 phenotypes ("predicted" from CYP2C9 genotypes and "measured" metabolic phenotype with a probe drug) among healthy volunteers according to their ethnicity and geographical distribution. Seventy-eight original research articles including a total of 31,978 subjects were identified. Expert opinion: CYP2C9*2 allele is the most frequent in Caucasian populations (average 14%), with the lowest frequencies for Africans (0.46%), East Asians (0.56%) and Native Americans (1.25%), which is in agreement with the hypothesis about the low prevalence in Amerindians. CYP2C9*3 shows the highest frequency among South Asians (11.7%), while CYP2C9*5 (1.56%) and *8 (4.70%) in African Americans. The predicted poor metabolizers (gPMs) were found overall in a low frequency, with the highest frequency detected for South Asians, in accordance with the CYP2C9*3 frequency in these populations. This study shows the worldwide variability in the CYP2C9 allele frequencies across different ethnic and geographic groups. Data about CYP2C9 "measured" metabolic phenotypes is still limited.